Ciri-ciri kejuruteraan, mineralogi dan mikrostruktur tanah liat lembut di Semenanjung Malaysia - Ahmad Tajudin, Saiful Azhar (2004)
Soft clay deposits are available along the west coast and some parts of the east coast of Peninsular Malaysia. Due to the increase in population and good economic growth, a lot of projects are implemented in these areas. Constructions on soft clays are often affected by stability and settlement problems. Therefore, in order to counter these problems, one has to know the engineering properties, mineralogy and the microstructure of the soft clay. Samples of soft clay for this study are taken at certain depth from construction sites being carried out along Peninsular Malaysia. This study is carried out to identify the engineering properties of soft clay such as soil index, consolidation characteristics, shear strength parameters, mineralogy and microstructure of the soil. Correlations and brief catalogues are produced to assist in the preliminary design process. X-rays diffraction (XRD) and X-rays fluorescence (XRF) are used to determine the mineralogy of soft clay. Scanning electron microscopy (SEM) is used to study the microstructure of clay. From this study, it can be concluded that the soft clays in the research area have high moisture content which reaches 139%. Whereas, the specific gravity (G,) is between 2.42 - 2.65, compressibility index (C,) is between 0.09 - 1.36, coefficient of consolidation (c,) is between 1.24 - 8.72 m21years and coefficient of volume compressibility (m,) is between 0.056 - 2.084 mZ/MN. The effective cohesion (c') values are in the range of 0 - 2 kN/m2, while the effective friction angle (I$') are in the range of 17" - 3 lo. Tests using XRD concludes that the primary mineral in soft clay is quartz and the secondary mineral is kaolinite. On the other hand, XRF tests shows that the quantity of silica oxide and aluminium oxide are quite high in soft clay, which are due to the presence of kaolinite mineral. Test using SEM verified the presence of kaolinite mineral and pyrite in soft clay. From the correlation derived, it shows that the compressibility index increases with natural moisture content, Atterberg limit, initial void ratio and organic content. On the other hand, the effective friction angle is found to be influenced by the natural moisture content and plasticity index. The correlation obtained shows that the effective friction angle decreases with increasing natural moisture content and plasticity index.